Microchip-based structure determination of low-molecular weight proteins using cryo-electron microscopy. Issue 15 (12th April 2021) - Casasanta, Michael A.; Jonaid, G. M.; Kaylor, Liam; Luqiu, William Y.; Solares, Maria J.; Schroen, Mariah L.; Dearnaley, William J.; Wilson, Jarad; Dukes, Madeline J.; Kelly, Deborah F.
Abstract : Here we show a major technical advance to study small proteins using cryo-EM. Structural models for the SARS-CoV-2 Nucleocapsid (N) protein are presented along with other coronavirus counterparts for therapeutic development. Abstract : Interest in cryo-Electron Microscopy (EM) imaging has skyrocketed in recent years due to its pristine views of macromolecules and materials. As advances in instrumentation and computing algorithms spurred this progress, there is renewed focus to address specimen-related challenges. Here we contribute a microchip-based toolkit to perform complementary structural and biochemical analysis on low-molecular weight proteins. As a model system, we used the SARS-CoV-2 nucleocapsid (N) protein (48 kDa) due to its stability and important role in therapeutic development. Cryo-EM structures of the N protein monomer revealed a flexible N-terminal "top hat" motif and a helical-rich C-terminal domain. To complement our structural findings, we engineered microchip-based immunoprecipitation assays that led to the discovery of the first antibody binding site on the N protein. The data also facilitated molecular modeling of a variety of pandemic and common cold-related coronavirus proteins. Such insights may guide future pandemic-preparedness protocols through immuno-engineering strategies to mitigate viral outbreaks.